Chronology of auditory processing and related co-activation in the orbitofrontal cortex depends on musical expertise - Bücher, Steffen; Bernhofs, Valdis; Thieme, Andrea; Christiner, Markus; Schneider, Peter (Frontiers in Neuroscience, 2023)
Using magnetoencephalography (MEG), we investigated the chronology of primary and secondary auditory processing and associated co-activation in the orbitofrontal cortex in a large cohort of 162 participants across of various ages. The sample consisted of 38 primary school children, 39 adolescents, 43 younger and 42 middle-aged adults, and was further divided into musically experienced participants and non-musicians by quantifying musical training and aptitude parameters. We observed that the coactivation in the orbitofrontal cortex (Brodmann-Area 10 (BA10)) depended strongly depended on musical expertise but not on age. In the musically experienced groups, a systematic coincidence of peak latencies of the primary auditory P1 response and the coactivated response in the orbitofrontal cortex was already observed in childhood at the onset of musical education. In marked contrast, in all non-musicians the orbitofrontal coactivation occurred 25-40 ms later as when compared to the P1 response. Musical practice and musical aptitude contributed rather equally to the observed activation and coactivation patterns in the auditory and orbitofrontal cortex, confirming the reciprocal, interrelated influence of nature and nurture in the musical brain. Based on the observed age-independent differences in the chronology and lateralization of neurological responses, we suggest that orbitofrontal functions may contribute to musical learning at an early age.